Can the acidic Ultisols in Peninsular Malaysia be alleviated by biochar treatment for corn cultivation? - Shamshuddin, Jusop; M. A., Rabileh; Che Ishak, Fauziah (Ilmiah Publishers, 2020)
Arable land in Peninsular Malaysia is dominated by highly weathered infertile soils which are taxonomically classified as Ultisols. The production of non-acid tolerant sweet corn on these acidic Ultisols is known to be negatively affected by soil acidity and/or Al3+ toxicity. However, to some extent, corn is able to defend itself against Al3+ toxicity and/or H+ stress. For Al3+ toxicity problem, the defence mechanism is along this line. The positively-charged Al3+ is attracted to the negatively-charged root surface of the sweet corn. When the Al3+ touches the surface of the root, the corn plant reacts instantly to release oxalic acid that chelates the Al3+. By this mechanism some of the Al3+ at the solution-root interface will be deactivated by the organic acid and rendered unavailable for uptake by corn. The chelation of Al3+ occurring in soil solution by this mechanism is a crucial step to help sustain the production of corn growing on the Ultisols. For sustainable corn production, the pH of the Ultisols has to be raised to a level above 5.3 by liming or other agronomic means. In the final analysis, Al3+ activity in the soil solution is less than the critical level of 10 µM. The low productivity of the Ultisols can be overcome by applying EFB-biochar at a rate of 10 t biochar/ha, which is an economically viable agronomic practice.